1986
DOI: 10.1128/aac.29.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the acyclic guanosine analog buciclovir [(R)-9-(3,4-dihydroxybutyl)guanine] in experimental genital herpes

Abstract: The efficacy of the anti-herpesvirus drug buciclovir [(R)-9-(3,4-dihydroxybutyl)guanineI was investigated in guinea pigs and mice infected intravaginally with herpes simplex virus type 2. Topical treatment initiated early after infection was efficacious, in contrast to topical treatment delayed 24 h or more. Systemic treatment of infected mice could not prevent the spread of virus to the brain and mortality. Systemically administered buciclovir had an effect in guinea pigs, even after delayed onset of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Indeed, when BCV was given subcutaneously in high doses (2 × 400 mg/kg/day) a beneficial effect against zoster development was obtained if treatment was started 72 h p.i. (Lundgren et al, 1986; data not shown). Nevertheless, in these experiments a maximum of 50~ reduction in zoster score was obtained, and therefore this treatment was less efficacious than treatment started 48 h p.i., when virus had already reached the sensory ganglia but not yet the skin of the lower flank (see Simmons & Nash, 1984).…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, when BCV was given subcutaneously in high doses (2 × 400 mg/kg/day) a beneficial effect against zoster development was obtained if treatment was started 72 h p.i. (Lundgren et al, 1986; data not shown). Nevertheless, in these experiments a maximum of 50~ reduction in zoster score was obtained, and therefore this treatment was less efficacious than treatment started 48 h p.i., when virus had already reached the sensory ganglia but not yet the skin of the lower flank (see Simmons & Nash, 1984).…”
Section: Discussionmentioning
confidence: 81%
“…Chiral acyclic nucleosides have received considerable attention because of their appealing biological activities and their usage as therapeutic agents for the treatment of HIV and hepatitis. 1–5 For example, ( R )-buciclovir is a specific inhibitor of the viral DNA polymerases in herpes simplex virus infection 2 and ( S )-cidofovir has been approved as an injectable medication for the treatment of cytomegalovirus (CMV) retinitis in AIDS patients. 3 d -Eritadenine is a potent inhibitor of S -adenosyl- l -homocysteine hydrolase 4 (Fig.…”
Section: Introductionmentioning
confidence: 99%